갑상샘 종양에서 hTERT 발현의 임상적 의의 - 김태원(Tae-Won Kim); 안창혁(Chang-Hyeok An); 김기환(Kee-Hwan Kim); 박우찬(Woo-Chan Park); 배자성(Ja-Seong Bae); 김정수(Jeong-Soo Kim) (Annals of surgical treatment and research, 2010)
Purpose: Telomerase is expressed by most malignancies including thyroid cancer. In this study, to evaluate the telomerase activity, we determine the expression of human telomerase reverse transcriptase (hTERT) in benign and malignant thyroid tumors. Methods: We examined the clinical data such as age, sex, and recurrence status of 100 patients that underwent thyroidectomy. Also, we reviewed the pathological data of the tissues (tumor size, lymph nodes, capsular invasion, perivascular invasion, perilymphatic invasion etc.). We checked hTERT expression by Allred scoring system using immunohistochemical staining. Results: 21 patients had benign thyroid nodules and 79 patients had malignant nodules. The average size of benign tumors and malignant tumors were 3.1±1.1 cm and 2.1±1.7 cm, respectively. The hTERT expression was higher in malignant tumors (82.3%) than in benign tumors (9.5%) and that difference was statistically significant. In metastatic lymph nodes status of thyroid cancers, 45 of 65 patients (69.2%) had lymphatic metastases in hTERT positive group, which is much higher than hTERT negative group (P=0.001). Conclusion: In our study, hTERT expression may be used as a prognostic biologic marker in thyroid cancer and also in the diagnosis of malignancy. Purpose: Telomerase is expressed by most malignancies including thyroid cancer. In this study, to evaluate the telomerase activity, we determine the expression of human telomerase reverse transcriptase (hTERT) in benign and malignant thyroid tumors. Methods: We examined the clinical data such as age, sex, and recurrence status of 100 patients that underwent thyroidectomy. Also, we reviewed the pathological data of the tissues (tumor size, lymph nodes, capsular invasion, perivascular invasion, perilymphatic invasion etc.). We checked hTERT expression by Allred scoring system using immunohistochemical staining. Results: 21 patients had benign thyroid nodules and 79 patients had malignant nodules. The average size of benign tumors and malignant tumors were 3.1±1.1 cm and 2.1±1.7 cm, respectively. The hTERT expression was higher in malignant tumors (82.3%) than in benign tumors (9.5%) and that difference was statistically significant. In metastatic lymph nodes status of thyroid cancers, 45 of 65 patients (69.2%) had lymphatic metastases in hTERT positive group, which is much higher than hTERT negative group (P=0.001). Conclusion: In our study, hTERT expression may be used as a prognostic biologic marker in thyroid cancer and also in the diagnosis of malignancy. KCI Citation Count: 0